Fibrilación auricular como factor de riesgo para mortalidad en enfermedad cerebrovascular isquémica en el Hospital Belén de Trujillo - Villanueva Medina, Franz Joset (2019)
Cerebrovascular disease is a worldwide pathology that affects all social groups and is one of the main causes of admission to hospitals. Ischemic type cerebrovascular disease constitutes a pathology of prevalence and significant incidence whose impact in terms of morbidity and mortality is very high; responsible for permanent disability, severe functional commitment generating absolute dependence and in the worst case scenario determining in-hospital mortality. Therefore, it is important to mention that atrial fibrillation (AF), besides being a risk factor for mortality in cerebrovascular disease, influences the prognosis of in-hospital evolution. The AF being the most frequent rhythm disorder in the population and that increases as the age of the individuals advances. Non-valvular AF increases the risk of ischemic stroke (CVA) 5 times, in addition to the ACV secondary to AF produce a high disability and mortality, so the prevention of these in these patients is a major public health concern. It is therefore of great interest to design and apply predictive elements that using resources accessible to our health environment such as clinical assessment as well as analytical assessments allow to select in the first hours of stay that group of patients with greater risk of presenting an unfavorable evolution to strengthen the monitoring behaviors as well as refining the corresponding therapeutic measures; this is why, being a problem of great relevance, the need to know the behavior of atrial fibrillation as a risk factor for mortality in ischemic cerebrovascular disease in the Belén Hospital of Trujillo is considered.